Recent trends in industrial and academic developments of green tyre technology - Bijina, V.; Jandas, P. J.; Joseph, Sherin; Gopu, J.; Abhitha, K.; John, Honey (Polymer bulletin (Berlin, Germany), 2023)
Growing natural calamities as a consequence of global warming are one of the most pondering subjects today. The exponential growth of environmental pollution due to unscientific human exploitation of natural resources is considered the prime reason for the harsh responses of nature. Researchers from various fields of industry and academia are working hard to develop and implement products/technologies that are environmentally friendly or less harmful to the ecosystem. Material researchers, specifically those working in the automobile sector are also not behind in search of green products from eco-friendly raw materials and production methods. The automobile industry is collectively responsible for around 40% of global pollution in terms of greenhouse gas emissions. Out of which around 20–30% is originating from tyre production and its end-use. In this view, tyre production from eco-friendly raw materials and technologies that have minimum hazardousness to the environment is a hot research topic today. A few products in the market with “green” tags and many are in the pipeline for the recent future. This review summarises a detailed discussion of the emerging green technologies for tyre production and depicted comprehensive data from the available literature. The paper has been drafted from a well-balanced academic and industrial point of view since the researchers from both sectors are working in harmony for a better future for green tyre technology.